TOURISTS’ PERCEPTION OF ELECTRIC BICYCLES AS AN ALTERNATIVE TRANSPORTATION MODE - Putra Ramadhan, Radhitya; Griselda Putri Widjanarko , Sandra; Suhendri , Ahmad (Fakultas Agama Islam Universitas Islam Al-Azhar, 2025)
Electric bicycles (e-bikes) are emerging as a vital solution in sustainable tourism, offering a balance between environmental preservation and modern mobility demands. This study focuses on tourists' perceptions of e-bikes as an alternative transportation mode in Gili Trawangan, a destination renowned for its eco-conscious policies. Employing a qualitative descriptive approach, it examines key factors influencing e-bike adoption, including usability, pricing strategies, infrastructure adequacy, and operational challenges. Tourists generally praised the lightweight and ergonomic design of e-bikes but highlighted concerns such as inconsistent maintenance, safety deficiencies, and limited charging stations. The analysis also reveals dissatisfaction with non-transparent pricing practices, emphasizing the need for standardized rates and flexible rental options. Recommendations include enhancing infrastructure, introducing safety measures, and launching educational initiatives to improve e-bike usage. By addressing these areas, e-bikes can significantly contribute to sustainable tourism, providing a replicable model for other eco-sensitive destinations globally.